Disaster Preparedness of Thai Migrants Living in Auckland: A Qualitative Descriptive Study - Pattanarattanamolee, Ratrawee (Auckland University of Technology, 2020)
Thai migrants are one of the diverse ethnic groups who live in New Zealand. Most Thai migrants live in Auckland, where faces heightened risks due to its exposure to natural hazards, such as flooding, storms, and tsunamis. Many studies indicate that migrants are generally more vulnerable in the face of natural hazards and disasters and they are less likely to prepare. On the other hand, several researches suggest that migrants are not without capacities in the face of such events. However, there is a small number of studies regarding the disaster preparedness of Thai migrants living in urban New Zealand. This study is a contribution towards filling this gap. A qualitative descriptive study was conducted with semi-structured interviews taking place in Auckland between September to December 2019. A total of seven Thai migrants, who have experience of natural hazards and/or disasters, were included in the study. The findings indicate that Thai migrants are vulnerable because of language and culture, low-risk perception, socioeconomic status, and low preparedness. On the other hand, the study emphasizes that Thai migrants have capacities, including strong bonding social network and their experience of previous disasters in their home country. The research concludes that disaster risk management targeting Thai migrants can be promoted by communicating information in Thai language and using the Thai temples as focal points for conducting activities geared towards disaster preparedness. Moreover, social media provide opportunities for sharing disaster-related information and promoting disaster risk education
Keywords: Disaster preparedness; Migrants; Thai; Qualitative study